Design of Door Security System Based on Face Recognition with Arduino - Januardi Nasir; Azizul Azhar Ramli; - Michael (JOIV : International Journal on Informatics Visualization, 2019)
Robotics technology is very useful for the lives of many people today. Almost all aspects of his life utilize robotics technology according to the required field. The development of robotics technology has become a higher quality of human life. Perhaps robotics are still less popular among the general public who still thinks robotics are humanoid robots (robots or human machines). Robotics has been widely implemented in the real world ranging from the fields of industry, medicine, entertainment, security, to household appliances. In the field of security, robotics has an important role. As the robot principle itself is tireless and has little tolerance, the product in robotics in the security field can be a very useful tool. In addition to facilitate human insecurity, robotics products can also facilitate human in various jobs, such as in the locking doors or walls of anyone who already exists. The development of robotics is in line with the development of computer vision which is increasing its application in everyday life. With this research, is expected to improve security and comfort in the security room. The design of this system using electronic door locks, open source OpenCV and webcam as a unit component.